PUSAT HIBURAN, EDUKASI DAN TEATER SEBAGAI RUANG INTERAKSI SOSIAL DI KAWASAN MANGGA BESAR - Tuju, Gilbertus Davy Ryan; Mustaram, Agnatasya Listianti (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
Since the Dutch era, Mangga Besar has been the center of entertainment destinations. There was once a park called Prinsen Park. This place became part of the history of theater and film, until it gave birth to the artist village "Tangkiwood". Now the place is gone and few people know about it. Prinsen Park began to be quiet since the era of analog television development. The surrounding environment was not organized and illegal settlements grew. Through rejuvenation, Prinsen Park was rebuilt into the Lokasari People's Entertainment Park (THR Lokasari). Now many shophouses are deserted and no longer operating. Until now, the place is also known negatively as a place of night entertainment for adults. The Mangga Besar Theater with a site location within the Lokasari area will create a positive and useful social interaction space by instilling memories of Prinsen Park through descriptive qualitative research methods. Education about theater arts and its history in Mangga Besar is carried out through schools around the area which are invited in turns to take part in training activities and presenting theater arts on stage. The target user visitors come from tourists to Mangga Besar and also the people of Jakarta who are assisted by adequate transportation such as trains. There is also a museum program and Prinsen Park History gallery, an art house with a recording studio and art workshops. Keywords:  education; entertainment; history; interaction; Lokasari Abstrak Sejak era Belanda, Mangga besar sudah menjadi pusat destinasi hiburan. Pernah terdapat sebuah taman dengan nama Prinsen Park. Tempat ini menjadi bagian dari sejarah teater dan perfilman, hingga melahirkan kampung artis “Tangkiwood”. Kini tempat itu sudah tidak ada dan sedikit yang mengetahuinya.  Prinsen Park mulai sepi semejak era perkembangan televisi analog. Lingkungan sekitarnya pun tidak tertata dan tumbuh pemukiman liar. Melalui peremajaan Prinsen Park diratakan dan dibangun kembali menjadi Taman Hiburan Rakyat Lokasari (THR Lokasari). Kini banyak ditemukan ruko sepi dan juga tidak beroperasi lagi.  Hingga saat ini tempat tersebut juga dikenal negatif sebagai tempat hiburan malam orang-orang dewasa. Teater Mangga Besar dengan lokasi tapak yang berada di lingkup kawasan Lokasari akan menciptakan ruang interaksi sosial yang positif dan bermanfaat dengan menanamkan memori Prinsen Park melalui metode penelitian kualitatif deskriptif. Edukasi mengenai seni teater dan sejarahnya di Mangga Besar dilakukan melalui sekolah-sekolah di sekitar kawasan yang diajak secara bergilir untuk ikut andil dalam aktivitas pelatihan dan menampilkan seni teater diatas panggung. Target user pengunjung berasal dari wisatawan Mangga Besar dan juga masyarakat Jakarta yang dibantu oleh transportasi yang memumpuni seperti Kereta. Terdapat juga program museum dan galeri Sejarah Prinsen Park, rumah seni dengan studio rekaman dan workshop seni.